Latent developmental and evolutionary shapes embedded within the grapevine leaf. Issue 1 (18th November 2015) - Chitwood, Daniel H.; Klein, Laura L.; O'Hanlon, Regan; Chacko, Steven; Greg, Matthew; Kitchen, Cassandra; Miller, Allison J.; Londo, Jason P.
Summary: Across plants, leaves exhibit profound diversity in shape. As a single leaf expands, its shape is in constant flux. Plants may also produce leaves with different shapes at successive nodes. In addition, leaf shape varies among individuals, populations and species as a result of evolutionary processes and environmental influences. Because leaf shape can vary in many different ways, theoretically, the effects of distinct developmental and evolutionary processes are separable, even within the shape of a single leaf. Here, we measured the shapes of > 3200 leaves representing > 270 vines from wild relatives of domesticated grape ( Vitis spp.) to determine whether leaf shapes attributable to genetics and development are separable from each other. We isolated latent shapes (multivariate signatures that vary independently from each other) embedded within the overall shape of leaves. These latent shapes can predict developmental stages independent from species identity and vice versa. Shapes predictive of development were then used to stage leaves from 1200 varieties of domesticated grape ( Vitis vinifera ), revealing that changes in timing underlie leaf shape diversity. Our results indicate that distinct latent shapes combine to produce a composite morphology in leaves, and that developmental and evolutionary contributions to shape vary independently from each other.